MANAJEMEN BANDWIDTH JARINGAN HOTSPOT PADA SMP MUHAMMADIYAH 6 MALANG - Roy Dafly Pirnadi; Sigit Kusmaryanto; Fakhriy Hario Partiansyah (Jurnal Mahasiswa TEUB, 2020)
Abstract— Wireless networks are an alternative in building practical networks. This technology is WLAN (wireless local area network) technology. The beginning of this technology uses a LAN (Local area network) that still uses cable media. This media has limitations that allow only a few devices to be connected. Therefore, over time, a technology was found that made it easier for users to be able to access the network without using cables or wireless networks. Channel settings make the existing signal quality will work optimally. Bandwidth management will make all users feel comfortable.IndexTerms—WLAN, Wireless, Management Bandwidth